Enhanced zebra optimization algorithm and applications of power allocation in SDWN - LI Jiajia; DONG Ligang; JIANG Xian (Dianxin kexue)
To address the issue of interference caused by shared resources in multi-user communications in software defined wireless network (SDWN), an enhanced zebra optimization algorithm (EZOA) was proposed to achieve power allocation that maximizes the secrecy rate. By introducing exploration factors and perturbation parameters into the zebra optimization algorithm, EZOA enhanced global search and local exploitation capabilities, while also improving the foraging strategy to increase algorithm diversity. Experimental results demonstrate that EZOA exhibits superior competitiveness compared to six other well-established algorithms on the IEEE CEC 2014 benchmark function set. In the SDWN power allocation problem, EZOA achieves an average improvement of 5.46% in user secrecy rate and the fastest convergence speed compared to five other algorithms.